1993
DOI: 10.1289/ehp.93101s233
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transfer of genotoxins and transplacental carcinogenesis.

Abstract: A number of chemical compounds induce cancer in the offspring of animals treated with these compounds. The fetus is sensitive to the toxic and teratogenic effects of chemicals in the early embryonic stages, whereas it is sensitive to carcinogenic effects during late fetal stages. Carcinogens may be direct acting or may require metabolic oxidation such as those in tobacco smoke. Activation can occur in utero. Animal experiments indicate that tumors can be initiated in utero, commonly by activation of cellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 29 publications
0
14
0
3
Order By: Relevance
“…Biological markers of exposure assessment to environmental carcinogens in the developing fetus have been limited previously to studies that have examined either placental exposure to carcinogens after delivery or the obtaining of biological specimens from the neonate (29,(84)(85)(86)(87)(88)(89)(90)(91). The latter process of using biological markers relies heavily on the obtaining of either meconium samples from the neonate after delivery, or small amounts of urine for analysis (92)(93)(94)(95)(96)(97)(98)(99).…”
Section: Introductionmentioning
confidence: 99%
“…Biological markers of exposure assessment to environmental carcinogens in the developing fetus have been limited previously to studies that have examined either placental exposure to carcinogens after delivery or the obtaining of biological specimens from the neonate (29,(84)(85)(86)(87)(88)(89)(90)(91). The latter process of using biological markers relies heavily on the obtaining of either meconium samples from the neonate after delivery, or small amounts of urine for analysis (92)(93)(94)(95)(96)(97)(98)(99).…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal exposure appears particularly hazardous [Rogan et al, 1986;Jacobson et al, 1990;Yu et al, 1991], although, one small study of prenatal DDE exposure showed no relation to preterm delivery [Berkowitz et al, 1996]. Animal studies demonstrating the transplacental transfer of genotoxins with subsequent teratogenic and carcinogenic effects also raise concern about in utero exposure to pesticides [Autrup, 1993]. The International Agency for Research on Cancer concluded that there was limited or suf®cient evidence for carcinogenicity of about half of the pesticides evaluated in experimental studies [IARC, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…[90][91][92] As(III) passes transplacentally and prenatal exposure to arsenic has been shown to increase risks of arsenic-related toxicity in early childhood and vulnerability to malignant and non-malignant pulmonary disease later in life. [93][94][95] Population studies in Argentina show that the methylation and excretion of arsenic are determined by genetic polymorphisms and expression of selected genes. 96 MMA is associated more with arsenic toxicity and bladder cancer but DMA has the lowest body retention of all As metabolites.…”
Section: Metabolismmentioning
confidence: 99%
“…Results of experiments in mice prompt further investigation into the potential risks posed to pregnant women in arsenic-rich countries. 93 …”
Section: Tissue Sensitivity Patterns In Methylation and Metabolism Ofmentioning
confidence: 99%